2014
DOI: 10.1103/physrevlett.112.197601
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Soft-Mode Vibrations of Lead Zirconate

Abstract: Polarized Raman, IR and time-domain THz spectroscopy of orthorhombic lead zirconate single crystals yielded a comprehensive picture of temperature-dependent quasiharmonic frequencies of its low-frequency phonon modes. It is argued that these modes primarily involve vibration of Pb and/or oxygen octahedra librations and their relation to particular phonon modes of the parent cubic phase is proposed. Counts of the observed IR and Raman active modes belonging to distinct irreducible representations agree quite we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
113
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 56 publications
(65 reference statements)
12
113
1
5
Order By: Relevance
“…It is also worthwhile to realize that the present work and model most likely are not fully applicable to PbZrO 3 (which is often considered to be the prototype of antiferroelectrics), even if a trilinear energy coupling has been documented there as well. 37,38 This is because it was recently proposed 39 that the unusual Pbam ground state of PbZrO 3 arises from an original bilinear coupling between antipolar motions and oxygen octahedral tiltings. As a result, Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worthwhile to realize that the present work and model most likely are not fully applicable to PbZrO 3 (which is often considered to be the prototype of antiferroelectrics), even if a trilinear energy coupling has been documented there as well. 37,38 This is because it was recently proposed 39 that the unusual Pbam ground state of PbZrO 3 arises from an original bilinear coupling between antipolar motions and oxygen octahedral tiltings. As a result, Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…PbZrO3 is the most representative antiferroelectric perovskite oxide. Recent lattice dynamic studies on this compound revealed rich information associated with the nature of the antiferroelectric phase transition [3][4][5][6]. In spite of the fact that the microscopic nature of the antiferroelectric phase transition in PbZrO3 is still under debate, it seems evident that more detailed and thorough investigations into the lattice dynamics over the whole momentum space in the Brillouin zone are indispensable for our better understanding of this archetypal antiferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these modes is labeled R + 4 according to its symmetry, and is rather simple: it features the typical antiphase tilting of the O 6 octahedra in the perovskite lattice. This mode is therefore associated with the zone-boundary 2π/a lat (1/2,1/2,1/2) k-point of the cubic first-Brillouin zone, where a lat is the lattice con- Recent works [6][7][8] suggest that a trilinear coupling between the predominant R (anti)polar displacements of the A cations in the perovskite lattice (Pb in PZO's case) and rotations of the O 6 octahedra. Remarkably, they can also explain and hold the key to understand many other non-trivial antipolar states (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…PZO's ground state displays the P bam symmetry and is mostly characterized by two strongly unstable soft phonon modes [6][7][8][9]12 . The first of these modes is labeled R + 4 according to its symmetry, and is rather simple: it features the typical antiphase tilting of the O 6 octahedra in the perovskite lattice.…”
Section: Introductionmentioning
confidence: 99%